Impaired self-recognition in individuals with no full-blown psychotic symptoms represented across the continuum of psychosis: a meta-analysis. Issue 16 (29th December 2021) - Lavallé, Layla; Dondé, Clément; Gawęda, Łukasz; Brunelin, Jérome; Mondino, Marine
Abstract: Background: Impairments in self-recognition (i.e. recognition of own thoughts and actions) have been repeatedly shown in individuals with schizophrenia. According to classical clinical characterizations, schizophrenia is included in a continuum encompassing a large range of genetic statuses, psychotic states and symptoms. The current meta-analysis aims to determine whether self-recognition is affected by individuals within the psychosis continuum. Method: Three populations were considered: people with an at-risk mental state for psychosis (ARMS), hallucination-prone individuals and unaffected relatives of patients with schizophrenia. Eleven studies contrasted self-recognition between these three populations ( n = 386) and healthy controls ( n = 315) and four studies used correlational analysis to estimate comparable effects ( n = 629). Eligible studies used experimental paradigms including source-monitoring and self-monitoring. Results: We observed significantly reduced self-recognition accuracy in these populations [ g = −0.44 (−0.71 to −0.17), p = 0.002] compared to controls. No influence of the type of population, experimental paradigm or study design was observed. Conclusion: The present analysis argues for self-recognition deficits in populations with no full-blown psychotic symptoms represented across the continuum of psychosis.